The postpartum depressive state in relation to perceived rearing: a prospective cohort study. - Norika Hayakawa (Public Library of Science (PLoS), 2012)
Background The relationship between perceived rearing and the postpartum depressive state remains unclear. We aimed to examine whether perceived rearing is a risk factor for postpartum depression as measured by the Edinburgh Postnatal Depression Scale (EPDS), and whether the score of perceived rearing is affected by depressive mood (the state dependency of perceived rearing). Methods Pregnant women (n = 448, mean age 31.8 ± 4.2 years) completed the EPDS as a measure of depressive state in early pregnancy (T1), late pregnancy (around 36 weeks), and at 1 month postpartum (T2), and the Parental Bonding Instrument (PBI) at T1 as a measure of perceived rearing. Changes in the EPDS and the PBI scores from T1 to T2 were compared between the non depressive (ND) group and the postpartum depressive (PD) group. Results There were no significant differences in any PBI category for perceived rearing between the ND and PD groups at T1. EPDS scores did not change significantly from T1 to T2 in the ND group but increased significantly in the PD group. The PBI maternal care score increased significantly in the ND group (p<0.01), while decreasing in the PD group (p<0.05). Additionally, in both the ND and PD groups, significant negative correlation was observed regarding change in the EPDS and PBI maternal care scores from T1 to T2 (r = -0.28, p = 0.013). Conclusions The present study suggests that perceived rearing is not a strong risk factor for postpartum depression as measured by the EPDS. Furthermore, the results indicated the state dependency of the PBI maternal care score.